Translating the Watcher’s Voice: Junot Díaz’s The Brief Wondrous Life of Oscar Wao into Spanish - Boyden, Michael; Goethals, Patrick (Meta, 2011)
This article offers an analysis of the Spanish translation of The Brief Wondrous Life of Oscar Wao by Dominican-American author Junot Díaz. We look at how the translation by Cuban author Achy Obejas affects the narrative situation, and in particular the solidarity relation between narrator and narratee. In the original, this solidarity relation depends on various forms of intra- and interlingual heteroglossia, which define the narrator’s voice as ethnically and racially marked. While the translation does to some degree neutralize this narrative voice, we argue that the Spanish version does not so much reduce as displace the solidarity effects embedded in the ST onto the relation between the implied author and reader of the TT. We further point attention to some of the differences between the two editions of the translation, directed at European and Latin American markets (Mondadori) and the North American market (Vintage Español) respectively. Surprisingly, the latter uses various paratextual insertions to construct an implied reader at some remove from the bilingual milieu in which the novel is set, and with which many Spanish-language readers in North America are highly familiar.